Financing transportation with land value taxes: Effects on development intensity - Junge, Jason R.; Levinson, David (Journal of Transport and Land Use, 2012)
A significant portion of local transportation funding comes from the property tax. The tax is conventionally assessed on both land and buildings, but transportation increases only the value of the land. A more direct, efficient way to fund transportation projects is to tax land at a higher rate than buildings. The lower tax on buildings would allow owners to retain more of the profits of their investment in construction, and have the expected side effect of increased development intensity. A partial equilibrium simulation is created for Minneapolis, Richfield and Bloomington, Minnesota to determine the intensity effects of various levels of split-rate property taxes for both residential and nonresidential development. The results indicate that split-rate taxes would lead to higher density for both types of development in all three cities.